PERHITUNGAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE ACTIVITY BASED COSTING (ABC) STUDI PADA PT. KARYA TIMUR PRIMA-MALANG - Hidayat, Wawan Wahyu (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the calculation of cost of production by using conventional methods and activity-based costing and know the difference and analyze the results of calculations between conventional methods with Activity Based Costing (ABC) method at PT. Karya Timur Prima. PT. Karya Timur Prima has done the calculation of cost of goods manufactured but the calculation of the cost of production is still less precise on the determination of raw material costs, direct labor costs, and overhead costs and there are costs that should not be included in the calculation.This research is a descriptive research with case study approach that is research that is intended to investigate the condition, condition or other things that have been mentioned that the result presented in research report. Data sources come from primary data. The data types used in this research are quantitative data and qualitative data. Data collection techniques used are observation, interview and documentation.The results of this research show difference calculation results between conventional and activity based costing methods in determining the cost of goods manufactured, which for the international potenza products 12 undercosted, in new potenza 16 undercosted and in potenza mild products 20 overcosted. Based on the conclusion, it can be considered that by using Activity Based Costing method, PT. Karya Timur Prima can calculate the cost of goods manufactured more accurately. Furthermore, activity based costing method is an alternative to maximize PT. Karya Timur Prima’s profits since the overhead costs are calculated based on the cost determiner of each activity which is incurred on each of its product.Keywords: Cost of Goods, Conventional, Activity Based Costing